Impacts of soil improvement on the pollutant-removal performance and DOM characteristics using a simulation experiment. (October 2019) - Yuan, Donghai; Zhou, Qiang; An, Yechen; Guo, Xujing; Chen, Bin; Wang, Saige; Wang, Sisi; Kou, Yingying; Li, Junqi
Highlights: Soil improvement showed a high water purification performance in the CTS than CSZ. DOM showed a relatively high humification and aromaticity in the CTS conditioner. The CTS improved soil was more effective in reducing fluorescent DOM than in CSW. The binding sites and sequences of DOM-metals can be influenced by soil improvement. The study can provide a guide for the treatment of agricultural NPS pollution. Abstract: An experimental simulation device was used to evaluate the water purification performance of soil improved with two different conditioners, which were cornstalk and zeolite (CSZ), turf and quartz sand (CTS) in this study. The results showed that the removal rates for total suspended solids (TSS), chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (TP) reached 75.58%, 25.71%, 68.37%, and 64.67%, respectively, for CSZ, and 85.09%, 92.75%, 76.71%, and 98.33%, respectively, for CTS, suggesting that soil improvement showed higher water purification performance with the CTS conditioner than with the CSZ conditioner. The structure, composition, and source of dissolved organic matter (DOM) were probed using ultraviolet visible (UV–Vis) spectra and fluorescence spectra. The spectral parameters indicated that the CTS conditioner-improved soil showed a relatively high humification and aromaticity of DOM, and a relatively higher contribution of organic matter derived from microbial substances. In addition, the results of 2D-COS suggested that the binding sites and sequences can be significantly influenced by soil improvement, and vary between the two kinds of conditioners. The CTS-improved soil was more effective in reducing fluorescent DOM than was the CSW-improved soil. This study can provide a scientific foundation for the treatment of agricultural non-point source (NPS) pollution.